Perancangan Startup Aqibers Platform Penyedia Jasa Aqiqah Metode Lean Startup - Fardian Anshori, Iedam; Sudjaja, Dinda Meilinda; Wibiksana, Haikal Andrean; Yahya , Taufik; Valentino, Dion Eko (MEANS (Media Informasi Analisa dan Sistem), 2024)
Startup Aqibers is a platform providing aqiqah services that uses the Lean Startup method in its design. This method is used to optimize innovation, efficiency and resource management. In the design phase, Startup Aqibers focuses on identifying market needs through in-depth research. StratupAqibers aims to simplify the aqiqah process by providing an online platform that makes it easier for users to choose an aqiqah package, confirm orders and make payments. Through the use of Lean Startup methods, Aqibers was able to identify the key features most desired by customers, improve user experience, and reduce product development risk. By leveraging continuous customer feedback, Aqibers was able to quickly iterate on its platform, ensuring that the solution they created offer in line with changing market needs. In this way, Aqibers is expected to achieve sustainable growth and provide significant added value for consumers who are looking for practical and reliable aqiqah services.